2016
DOI: 10.24953/turkjped.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Type of setting for the inpatient adolescent with an eating disorder: Are specialized inpatient clinics a must or will the pediatric ward do?

Abstract: There are a range of different services for treating adolescent eating disorders (ED) but there is no clinical consensus and a paucity of research indicating which type of treatment setting is the best. Although it would be ideal to have a specialized ward for these patients what happens when this is not possible? The aim of this study was to evaluate patients with ED hospitalized on a general pediatric ward. A retrospective chart review for 37 patients hospitalized for an ED and followed by a team consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In 13 studies, the necessity of close observation of service users – particularly in inpatient environments (Akgül et al, ) – and a sense of being observed in turn, resulted in interpersonal mistrust amid a culture of surveillance. Participants described feeling awkward about intently monitoring service users to prevent ED behaviors: “They have to have somebody sitting in their room all day long with them….I feel uncomfortable for them” (nurse; Harken et al, , p. e38).…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, the necessity of close observation of service users – particularly in inpatient environments (Akgül et al, ) – and a sense of being observed in turn, resulted in interpersonal mistrust amid a culture of surveillance. Participants described feeling awkward about intently monitoring service users to prevent ED behaviors: “They have to have somebody sitting in their room all day long with them….I feel uncomfortable for them” (nurse; Harken et al, , p. e38).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely to this, Akgul and colleagues 24 stated that the average time YP required NG feeding was 2.5 days when treated on a paediatric ward.…”
Section: Length Of Time On Ng Feeding / Weaningmentioning
confidence: 95%
“…In 13 studies in which NG was not the independent variable, the proportion of ED YP requiring NG feeding was between 6% -66%. 3,7,17,[22][23][24][25][26][31][32][33]38,42 Nehring and colleagues 26 found that NG feeding was more likely to be required in: patients of a lower age at admission (14.3 compared to 15.3 years old, P<0.05), those with a shorter time period between disease onset and admission to hospital (P<0.0001), and longer time since last discharge (P<0.05). NG feeding is required more commonly in Early onset (EO) AN than adult onset (20% compared to 0%, P<0.05).…”
Section: Prevalence and Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations